Breeding for blast-disease-resistant and high-yield Thai jasmine rice (Oryza sativa L. cv. KDML 105) mutants using low-energy ion beams - S. Mahadtanapuk (2018)
Low-energy ion beam was applied on mutation induction for plant breeding of blast-disease-resistant Thai jasmine rice (Oryza sativa L. cv. KDML 105). Seeds of the wild-type rice were bombarded in vacuum by nitrogen ion beam at energy of 60-80 keV to a beam fluence range of 2 × 1016-2 × 1017 ions/cm2. The ion-bombarded rice seeds were grown in soil for 2 weeks as transplanted rice in plastic pots at 1 seedling/pot. The seedlings were then screened for blast resistance by Pyricularia grisea inoculation with 106 - spores/ml concentrations. The blast-resistant rice mutant was planted up to F6 generation with the consistent phenotypic variation. The high percentage of the blast-disease-resistant rice was analyzed with DNA fingerprint. The HAT-RAPD (high annealing temperature-random amplified polymorphic DNA) marker revealed the modified polymorphism fragment presenting in the mutant compared with wild type (KDML 105). The cDNA fingerprints were investigated and the polymorphism fragment was subcloned into pGEM-T easy vector and then sequenced. The sequence of this fragment was compared with those already contained in the database, and the fragment was found to be related to the Spotted leaf protein 11 (Spl11). © 2013 Published by Elsevier B.V.